MARKETING STRATEGY FOR PRODUCTS RESULTING FROM INDEPENDENCE BUILDING THROUGH SOCIAL MEDIA AND E-COMMERCE AT THE MALANG CLASS I CORRECTIONAL INSTITUTION - Abyan Lazuardi Al Faruq; Naniek Pangestuti (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the marketing strategy for products made by inmates through social media and e-commerce at Malang Class I Correctional Institution. The research uses a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The findings indicate that the correctional institution has implemented the marketing mix concept (product, price, place, and promotion) in its digital marketing strategy. Products produced by inmates demonstrate good market potential; however, several challenges remain, including limited stock management, insufficient digital promotion, and distribution systems that have not yet operated optimally. Although social media and e-commerce platforms such as Instagram and Shopee have been utilized, their use has not been fully optimized due to limitations in human resources and digital infrastructure. Despite these challenges, the marketing strategy has contributed positively to inmate empowerment and improved the public image of the institution. Therefore, improvements in digital content management, employee training in digital marketing skills, and strengthening of the distribution system are necessary to achieve more effective and sustainable marketing outcomes. Keywords: Digital Marketing; Independence Training; Correctional Institutions; Social Media; E-Commerce; Prisoners